Road safety education for schools with ZoSS facilities in Bandung City, Jawa Barat - Elly Adriani Sinaga; Sita Aniisah Sholihah; Rehani Fitrina; Sarinah Sihombing; Prima Widyanto (Universitas Muhammadiyah Magelang, 2022)
West Java is the province in Indonesia with the third greatest number of accidents. Accidents are caused by dangerous traffic behavior. In order to save Indonesia's productive generation, changing traffic behavior is a top concern. Several schools in accident-prone areas have been designated as Safe School Zones (ZoSS) by the government. However, it is vital to teach students and their support systems how to drive safely. This program seeks to promote road safety knowledge and behavior, support changes in traffic safety behavior, and increase traffic safety knowledge and behavior among students, teachers, and the public. On December 22, 2021, the activity was held in 5 elementary schools (SD) and 5 junior high schools (SMP), with theoretical and practical road safety training. The activities resulted in the development of young fighters' capacity, the formation of Road Safety Ambassadors and Safety Awareness Community Groups (KMSK), and the emergence of a sustainable program by advocating to the government and designating the Bandung City Transportation Office as the Adopting Father of Ambassadors and KMSK.